How to interpret liver function tests in heart failure patients? - Çağlı, Kumral; Başar, Fatma Nurcan; Tok, Derya; Turak, Osman; Başar, Ömer (Turkish Journal of Gastroenterology, 2015)
Abstract Cardiac hepatopathy has generally been used to describe any liver damage caused by cardiac disorders in the absence of other possible causes of liver damage. Although there is no consensus on the terminology used, cardiac hepatopathy can be examined as congestive hepatopathy (CH) and acute cardiogenic liver injury (ACLI). CH is caused by passive venous congestion of the liver that generally occurs in the setting of chronic cardiac conditions such as chronic HF, constrictive pericarditis, tricuspid regurgitation, or right-sided heart failure (HF) of any cause, and ACLI is most commonly associated with acute cardiocirculatory failure resulting from acute myocardial infarction, acute decompensated HF, or myocarditis. Histologically, CH is characterized by sinusoidal dilation, replacement of hepatocytes with red blood cells extravasating from the sinusoids, and necrosis/apoptosis of zone 3 of the Rappaport acinus, and it could progress to cirrhosis in advanced cases. In ACLI, however, massive necrosis of zone 3 is the main histological finding. Primary laboratory findings of CH are elevated serum cholestasis markers including bilirubin, alkaline phosphatase, and γ-glutamyl-transpeptidase levels, whereas those of ACLI are a striking elevation in transaminase and lactate dehydrogenase levels. Both CH and ACLI have a prognostic value for identifying cardiovascular events and mortality and have some special implications in the management of patients undergoing ventricular assist device implantation or cardiac transplantation. There is no specific treatment for CH or ACLI other than treatment of the underlying cardiac disorder.